Alginate-aker injectable composite hydrogels promoted irregular bone regeneration through stem cell recruitment and osteogenic differentiation. Issue 13 (14th March 2018) - Zhang, Xiangkai; Zhu, Yanlun; Cao, Lingyan; Wang, Xiao; Zheng, Ao; Chang, Jiang; Wu, Jiannan; Wen, Jin; Jiang, Xinquan; Li, Haiyan; Zhang, Zhiyuan
Abstract : With SAG usage, the hBMSC migration ability was stimulated through CXCR4 elevation while osteogenic differentiation was promoted via the ERK signaling pathway. Abstract : Recent studies have unveiled the unique osteogenesis and angiogenesis abilities of akermanite. However, such bioceramics rarely fit well into irregularly shaped bony cavities (such as bone defects and the maxillary sinus). In this study, an injectable hydrogel SAG system containing sodium alginate, akermanite and glutamate was prepared and evaluated in such defects. Cell proliferation experiments showed that except for stoste, the other extracts showed no cytotoxicity at various concentrations. In addition, the gene expression of Runx2 (runt-related transcription factor-2), BMP-2 (bone morphogenetic protein-2), ALP (alkaline phosphatase), and BSP (bone sialoprotein) and the activity of ALP were significantly higher in human bone marrow stromal cells (hBMSCs) cultured with 1/2 hydrogel extracts containing 66.9 ppm calcium ions, 23.8 ppm magnesium ions and 33.5 ppm silicon ions compared to those in hBMSCs cultured with the control medium, which indicated that the hydrogel extracts could stimulate the osteogenic differentiation of hBMSCs. Further experiments revealed that the ERK signaling pathway was engaged in osteogenic differentiation as early as 15 minutes after incubation with the hydrogel extracts. In addition, hBMSCs incubated in half-diluted extracts exhibited an almost doubled migration ability compared with the hBMSCs in the control group. More specifically, compared to the control group, hBMSCs cultured with 1/2 hydrogel extracts showed a 7% increase and a 10-fold increase in the protein and gene levels of CXCR4 (C-X-C chemokine receptor type 4), respectively. In vivo tests demonstrated that the bone formation rate of SAG hydrogels injected alone was similar to that of its counterpart seeded with BMSCs, reaching 24% at three months after operation. Therefore, it could be concluded that SAG hydrogels contribute to bone regeneration by not only promoting osteogenic differentiation but also by enhancing the recruitment of BMSCs to defect sites, making the injectable SAG hydrogels competent for the regeneration of irregular bony cavities.